Leptin, adiponectin and insulin as regulators for energy metabolism in a rat model of metabolic syndrome - Wong, Sok Kuan; Chin, Kok Yong; Ima-Nirwana Soelaiman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Leptin, adiponectin, and insulin are pivotal regulators for lipid and glucose metabolism. This study aimed to investigate the changes in these hormones in a rat model of metabolic syndrome (MetS) induced by high-carbohydrate high-fat (HCHF) diet. Twelve-week-old male Wistar rats were divided into two experimental groups. The normal group was given standard rat chow with tap water. The HCHF group was given HCHF diet with 25% fructose-supplemented drinking water to induce MetS. Body composition of the animals was measured using dual-energy X-ray absorptiometry. Blood was collected at week 0, 8, 12, and 16 for the measurement of blood glucose and hormone levels. Our findings demonstrated that HCHF diet significantly increased fat mass, percentage of fat, and decreased lean mass in the animals starting from week 8. The levels of blood glucose, leptin, and insulin were significantly higher but the level of adiponectin was significantly lower in the HCHF rats compared to the normal rats. In conclusion, hormones play a key underlying role in regulating lipid and glucose metabolism in MetS.